Aplikasi E-Booking Hello Studio Foto Berbasis Android - Wisnu Mukti Dwiyudho Putro; Ade Dwi Putra; Donaya Pasha (Swarnadwipa, 2024)
E-Booking is an online-based ordering concept carried out via android. Today's very rapid technological advances have resulted in demands for an industry or organization to be able to manage data precisely, quickly and accurately. So that you can create the output or results you want to achieve with what is expected. This makes it easier for customers when making photo studio order transactions by doing it quickly and efficiently. Likewise, admins can easily manage package type data, customer data and data. order transactions. The method used in designing this system is the Extreme Programming method. The results of system testing using black box testing show that the system has run according to the expected results. Apart from black box testing, system testing using the ISO 25010 test, shows that the system obtained a total average of 87.75%.